2012
DOI: 10.1016/j.jsat.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention for drug-abusing adolescents in a school setting: Outcomes and mediating factors

Abstract: This randomized controlled trial evaluated the use of two brief intervention conditions for adolescents (aged 12–18 years) who have been identified in a school setting as abusing alcohol and other drugs. Adolescents and their parent (N = 315) were randomly assigned to receive either a 2-session adolescent only (BI-A), 2-session adolescent and additional parent session (BI-AP), or assessment only control condition (CON). Interventions were manually guided and delivered in a school setting by trained counselors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
2
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(153 citation statements)
references
References 43 publications
4
123
2
13
Order By: Relevance
“…Winters, Fahnhorst, Botzet, Lee, and Lalone (2012) reported that both MI Only (two sessions with adolescent alone) and MI þ Parent (adding one session with a primary guardian) were superior to assessment-only control in reducing ASU in school settings, with MI þ Parent exhibiting greater and more consistent effects than MI Only. The other studies examined standalone MET.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…Winters, Fahnhorst, Botzet, Lee, and Lalone (2012) reported that both MI Only (two sessions with adolescent alone) and MI þ Parent (adding one session with a primary guardian) were superior to assessment-only control in reducing ASU in school settings, with MI þ Parent exhibiting greater and more consistent effects than MI Only. The other studies examined standalone MET.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…La literatura científica nacional e internacional seña-la que la consejería breve, es decir una sola sesión de 30 minutos, puede motivar el cambio en etapas iniciales del consumo (Martínez et al, 2010;Tavera & Martínez, 2008;Timko, Kong, Vittorio, & Cucciare, 2016;Winters, Fahnhorst, Botzet, Lee, & Lalone, 2012). Sin embargo, valdría la pena profundizar en esta hipótesis y determinar qué tanto una sola sesión bien estructurada puede lograr una transformación en los jóvenes que se inician en el uso de sustancias.…”
Section: Conclusionesunclassified
“…Embora estudos nacionais e internacionais apontem a eficácia e eficiência da utilização de instrumentos de rastreamento para o consumo de álcool associados à IB [8][9][10][11][12][13][14] , outros demonstram a existência de dificuldades para implementá-los na atenção primária à saúde, em decorrência da falta de conhecimento e preparo dos profissionais da equipe de saúde 8,15 . Tal fato, demonstra a necessidade de capacitações e treinamentos constantes, com o objetivo de rever conceitos e atitudes dos trabalhadores de saúde frente aos usuários de álcool 16 .…”
Section: Introductionunclassified